The Impact of Different Types of Innovation on Sustainable Development: An Empirical Study of Industrial Companies - A.V. Trachuk; N.V. Linder (Communications of International Proceedings, 2020)
The article is devoted to the study of the impact of various types of innovations on sustainable development of industrial companies. The empirical analysis is based on data from 123 industrial companies (167 respondents). For the analysis, factorial and regression methods were used, which makes it possible to assess the dependence of various types of innovations on the enterprise efficiency. Within the framework of this study, three resultant indicators of industrial companies sustainable development have been distinguished: the share of sustainable products in the total output, the level of reduction in resource consumption, and the development of qualified employees. This approach made it possible to conduct a comprehensive analysis of innovation activities and analyze the impact of each type of innovation on the industrial enterprises sustainable development indicators. The obtained results showed: (1) all types of innovations at enterprises are interconnected: product and technological innovations are positively interconnected with management innovations, and the intensity of management innovations leads to organizational innovations, (2) the increase in the sustainable products share is more influenced by product and technological innovations, resource consumption reduction - with technological and organizational, and qualified employees development – with managerial innovations. The conclusions made will allow industrial enterprises, depending on their strategic goals, to combine investments in certain types of innovative activities and thereby achieve the goals of sustainable development. Understanding the complex nature of innovation will enable businesses to build long-term competitive advantages.
Keywords: Innovation; Product Innovation; Technological Innovation; Organizational Innovation; Managerial Innovation; Sustainable Development; Industry.